Work and migration : life and livelihoods in a globalizing world - Sørensen, Ninna Nyberg; Olwig, Karen Fog, 1948- (London ; New York : Routledge, 2003)
Using case studies from those who have moved either transnationally or within their own country, international contributions offer various definitions of what it means to make a living on the move.
Using case-studies from those who have moved either transnationally or internally within their own country, international contributors offer various definitions of what it means to make a living on the move. Using case-studies from those who have moved either transnationally or internally within their own country, international contributors offer various definitions of what it means to make a living on the move.
Mobile livelihoods: making a living in the world / Karen Fog Olwig & Ninna Nyberg Sørensen -- Representing the local: mobile livelihood practices in the Peruvian Central Sierra / Ninna Nyberg Sørensen -- Mobile minds and socio-economic barriers: livelihoods and African-American identification among youth in Nairobi / Bodil Folke Frederiksen -- Mobility, rootedness, and the Caribbean higgler: production, consumption and transnational livelihoods / Carla Freeman -- A "respectable" livelihood: mobility and identity in a Caribbean family / Karen Fog Olwig -- "You must win their affection ... ": migrants' social and cultural practices between Peru and Italy / Carla Tamagno -- Business as usual: livelihood strategies and migration practice in the Peruvian diaspora / Karsten Paerregaard -- The moving "expert": a study of mobile professionals in the Cayman Islands and North America / Vered Amit -- Irse pa' fuera: the mobile livelihoods of circular migrants between Puerto Rico and the United States / Jorge Duany -- Transnational livelihoods and identities in return migration to the Caribbean: the case of skilled returnees to Jamaica / Elizabeth Thomas-Hope -- The final move?--Displaced livelihoods and collective returns in Peru and Guatemala / Finn Stepputat.
Originally published 2002 by Routledge.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Foreign workers; Emigration and immigration -- Economic aspects; Globalization -- Economic aspects; Émigration et immigration -- Aspect économique.; Mondialisation; Travailleurs étrangers.; globalism; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Emigration and immigration -- Economic aspects; Foreign workers; Globalization -- Economic aspects; Employment opportunities; Migrant workers; Rural-urban migration; Professional workers; Return migration; Income sources